Effects of Visual Noise on Binocular Summation in Patients With Strabismus Without Amblyopia - Pineles, Stacy L. (2014)
PURPOSE: Patients with strabismus often complain of difficulty navigating through visually stimulating environments without clear explanation for this symptom. Binocular summation (BiS), defined as the superiority of binocular over monocular viewing on visual threshold tasks, is decreased in conditions that cause large interocular differences in visual acuity, but is not well studied in strabismic populations without amblyopia. The authors hypothesized that strabismus may lead to decreased BiS for tasks related to discrimination within increased background complexity. The goal of this study was to test the extent of BiS in patients with strabismus during discrimination of a luminance target disk embedded in visual noise. METHODS: Participants included 10 exotropic, 10 esotropic, and 13 age-matched control patients. Performance of a task detecting a luminance-target was measured at 0, 10, and 20 μdeg(2) of visual noise for binocular and monocular conditions. BiS was calculated as the ratio of binocular contrast sensitivity to monocular contrast sensitivity for the target embedded in noise. RESULTS: Patients with strabismus had lower BiS values than controls, with a significant decrease on linear regression in patients with strabismus at 20 μdeg(2) of noise (P = .05), with a trend toward significance at 10 μdeg(2) of noise (P = .07). Patients with strabismus showed a mean binocular inhibition (summation ratio < 1) at both noise levels. CONCLUSIONS: These findings support the hypothesis that strabismus can lead to decreased BiS and even binocular inhibition. Despite literature showing enhanced BiS in visually demanding situations such as high levels of visual noise or low contrast, BiS was not significantly affected by visual noise in either group.